Pengaruh Green Perceived Value, Green Perceived Risk, Green Consumer Consfusion, Green Trust, Consumer Guilt, Self Monitoring, Pride Dan Perceived Consumer Effectiveness Terhadap Green Purchase Intention (Kasus Starbucks Jakarta) - Feliks Antonius (Jurnal Manajemen Bisnis dan Kewirausahaan, 2019)
The research aims to find out the relationship between green perceived value, green perceived risk, green consumer consfusion, green trust, consumer guilt, self monitoring, pride and perceived consumer effectiveness to green purchase intention in Starbucks Jakarta.  The method used in sampling is non-probability sampling method with purposive sampling technique which is a sampling technique by selecting sampling unit on the basis of certain criteria. The period of questionaire taking starts in May-September 2017. The data obtained will be analyze using Structural Equation Modeling (SEM). The conclusion  of this study indicates green perceived value and green perceived risk have significant influence to green trust. Consumer guilt, self monitoring and pride have significant effect to perceived consumer effectiveness on product Starbucks. Green trust and perceived consumer effectiveness as intervening variable at significance 5%. More specifically, the effect of green consumer confusion on green trust is not significant and the effect of green trust on green purchase intention is not significant too. The sum of increasing perceived consumer effectiveness then increasing green purchase intention.